2021
DOI: 10.3390/w13192615
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Curves for Slope Stability of Geogrid Reinforced River Levees

Abstract: When constructing flood protection structures such as river levees, oftentimes due to various factors engineers must design composite structures, i.e., reinforced earthen structures which comply with all the stability criteria. The most common way of reinforcing such structures is the usage of geosynthetics, or mostly geogrids when talking about stability. Since geosynthetics are man-made materials produced in a controlled environment and go through quality control measures, their characteristics contain a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Geogrid also used in reinforced backfill with gabion faced retaining wall for stabilization of slope (Wang et al 2021). Another important application of geogrid to stabilize the slope on a river levee in northen Croatia (Rossi et al 2021). To increase the stability of land fill slope, geogrid plays crucial role (Cortellazzo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Geogrid also used in reinforced backfill with gabion faced retaining wall for stabilization of slope (Wang et al 2021). Another important application of geogrid to stabilize the slope on a river levee in northen Croatia (Rossi et al 2021). To increase the stability of land fill slope, geogrid plays crucial role (Cortellazzo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of only the observed extreme values often leads to unrealistic levee section and material parameters, and if numerical analyses are used to obtain results, this leads to numerical problems and thus results are impossible to acquire. Additionally, the relationships of deformations and other responses to all the input parameters are highly non-linear, similar to the function of safety factors shown in Rossi et al [17]. Since the SB is based on a linear metamodel, this would cause the model to be unfit for the data and as a result give incorrect factor importances.…”
Section: Physical and Mechanical Hydraulicmentioning
confidence: 76%
“…Three papers are directly related to the development of fragility curves that are necessary for the risk assessment [9][10][11]. The fragility curves represent the probability of failure, or a certain level of damage, depending on a parameter that defines the intensity of the main action that might cause the failure.…”
mentioning
confidence: 99%
“…Fragility curves for river levees reinforced with geogrid, related to slope stability, were developed by Rossi et al [10]. They concluded that the global uncertainty is much more conditioned by the uncertainty of the friction angle value of the dam material than that associated with the geogrid material.…”
mentioning
confidence: 99%